(untitled) (Journal of Accounting and Financial Studies ( JAFS ), 2022)
The research aims to reveal the availability of skills to develop the tax assessor when carrying out the tax examination process. The study was conducted in the branches of the General Tax Authority in the province of Baghdad (the General Authority for Taxes, Adhamiya branch, the General Authority for Taxes, Rusafa branch, Al-Bayaa branch, New Baghdad tax branch) was approved The descriptive approach to achieve the research objectives represented by answering the following two questions: 1- What are the necessary skills that should be available in the performance of the tax examiner? 2- Are the skills of developing a tax evaluator available? The two researchers used the closed questionnaire as a tool for their research. The questionnaire included five areas (cognitive skills, technical skill, self-management skills, professional skills and interpersonal skills). Each skill consisted of a number of paragraphs, as the total number of paragraphs reached (23) items distributed according to its fields, a random sample of (66) was selected from the research community represented by workers in the branches of the General Authority for Taxes. The results of data analysis using the statistical program were shown ( SPSS V.21) Cognitive skills, professional and technical competence, communication skill, self-management and interpersonal skill are available in the study sample. But it is not enough for the tax examiner to be able to reduce tax objections, improve the tax examination process, and confirm the credibility of financial reports, in addition to the weakness in the effectiveness of the tax examination process. This is due to several reasons, the most important of which is the limited number of cadres working within the field of tax examination, weakness In the application and interpretation of tax laws and legislation when preparing the tax return due to the lack of experience of some assessors. The research reached several recommendations, the most important of which is the interest in the quality of students accepted to study in universities and the need to include accounting and financial standards within the curriculum and attention to the scientific qualification of the tax assessor through knowledge of legislation and tax laws, and increasing the number of examiners working in the assessment units in the branches of the authority in proportion to the size of the workload in the form Which makes time constraints the cornerstone of achieving quality.